Konsep Diri Remaja Cina Benteng (Studi Komunikasi Pada Remaja Cina Benteng di Tangerang) - Sheren Millennia Wijaya; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Indonesia is a plural country because it has a variety of ethnicities, languages, religions. One of the ethnic groups in Indonesia is Benteng Chinese who have lived for a long time in Tangerang. Each ethnic group has its own identity or uniqueness that differentiates it from other ethnicities. Benteng Chinese society consists of various groups, one of which is a teenager. One of the most important periods in this phase of human life occurs in adolescence. During this period, a teenager's mental development and growth process occurs to form an identity that will describe his self-concept. Every teenager has a different self-concept. Parents are the biggest factor in the formation of adolescent self-concept. Imitation also affects self-concept. The purpose of this study was to describe the self-concept of Benteng Chinese Youth and what factors influence the self-concept of Benteng Chinese youths. In examining this research the writer uses concepts and theories, namely self-concept, imitation, adolescence, and Cina Benteng. This research uses a qualitative approach with a case study method. The research data was obtained through interviews with two key informants and two supporting informants, as well as a literature study. The results showed that the self-concept possessed by Chinese Benteng youths varied physically, socially, and psychologically. And the factor that most influences the formation of adolescent self-concept is parents. adolescence, and Cina Benteng. This research uses a qualitative approach with a case study method. The research data was obtained through interviews with two key informants and two supporting informants, as well as a literature study. The results showed that the self-concept possessed by Chinese Benteng youths varied physically, socially, and psychologically. And the factor that most influences the formation of adolescent self-concept is parents. adolescence, and Cina Benteng. This research uses a qualitative approach with a case study method. The research data was obtained through interviews with two key informants and two supporting informants, as well as a literature study. The results showed that the self-concept possessed by Chinese Benteng youths varied physically, socially, and psychologically. And the factor that most influences the formation of adolescent self-concept is parents.Indonesia merupakan negara majemuk karena memiliki beragam suku, etnis, bahasa, agama. Salah satu etnis yang ada di Indonesia adalah Cina Benteng yang sudah menetap lama di Tangerang. Setiap etnis memiliki identitas atau keunikan masing-masing yang membedakan dengan etnis lainnya. Masyarakat Cina Benteng terdiri dari berbagai kalangan, salah satunya remaja. Salah satu periode terpenting dalam fase kehidupan manusia terjadi pada masa remaja. Pada masa ini terjadi proses perkembangan dan pertumbuhan mental seorang remaja sehingga membentuk jati diri yang akan menggambarkan konsep dirinya. Setiap remaja memiliki konsep diri yang berbeda-beda. Orang tua merupakan faktor terbesar terbentuknya konsep diri remaja. Imitasi juga berpengaruh terhadap konsep diri. Tujuan dari penelitian ini adalah untuk mengetahui gambaran konsep diri Remaja Cina Benteng dan faktor apa saja yang mempengaruhi terbentuknya konsep diri remaja Cina Benteng. Dalam mengkaji penelitian ini penulis menggunakan konsep dan teori yaitu konsep diri, imitasi, remaja, dan Cina Benteng. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data penelitian diperoleh melalui wawancara terhadap dua key informan dan dua informan pendukung, serta studi kepustakaan. Hasil penelitian menunjukkan bahwa konsep diri yang dimiliki remaja Cina Benteng berbeda-beda secara fisik, sosial, maupun psikologis. Dan faktor yang paling berpengaruh terhadap pembentukan konsep diri remaja adalah orang tua.